MEMBANGUN TAMAN LITERASI ECOBRICK SEBAGAI RUANG PUBLIK BERKELANJUTAN - Hafizd, Jefik; Purnama S, Mei Linda; Oktaviani, Tabitha; Nuryani, Nuryani; B.A.P, Silvy Kanawanti; Amelia, Rika; Karim, Noer M. Abdul; Azriyah, Azriyah; Normalia, Nita; Wibisono, Ian Ainun; Noviyanti, Alinda; Nurherawati, Irma; Guna, Bayu Cakra; Widyawati, Inayah; A, Mohamad Fajar; Febiana, Via (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
Warukawung Village, Depok District, Cirebon Regency, holds significant potential in education, the furniture industry, and the environment but faces challenges such as low reading interest, plastic waste management, and limited skills in furniture business management. This article discusses the Community Service Program (KKN) initiative aimed at addressing these issues through two main programs: Ecobrick education and the construction of the Ecobrick Literacy Park. The Participatory Action Research (PAR) method was employed, involving active participation from the community at every stage, from planning to evaluation. The Ecobrick education program at SDN 1 Warukawung involved 5th-grade students to raise environmental awareness and provide plastic waste management skills, where students were taught to create Ecobricks, later used to beautify the school garden. The Ecobrick Literacy Park project at the Warukawung Village Hall created a public space that supports literacy activities and promotes environmental awareness. Using Ecobricks for park elements such as benches, tables, and bookshelves, the park also includes a mini-library made from Ecobricks. Through the PAR approach, community participation ensured that the program was relevant and beneficial. The outcomes successfully improved the quality of education, environmental awareness, and community empowerment, providing long-term benefits for the village. Sustainability recommendations include regular teacher training, environmental education programs, and the formation of a literacy park maintenance group to ensure lasting benefits for the community.